Effect of wheel grinder on the surface roughness when grinding aluminum alloy - Muhamad Afiq, Razali (2010)
Grinding is one of the most complex processes in machining operation. Usually it is use for the finishing process to give the best surface finish and accurate dimension to the product by removing small amount of material on surface. It is important for the product because it will be influence to the quality of the product. The purpose of this study is to investigate the effect of the surface roughness on the 1060 aluminum alloy when using different depth of cut, worktable speed and different type of wheel. The others purpose is to find the optimization parameters that effect to the surface roughness of the 1060 aluminum alloy. Precision surface grinding machine is use to grind the aluminum alloy. Taguchi method and analysis of variance (ANOVA) are use to analyze the result for experiments. From the result, it shows the highest worktable speed and depth of cut give the highest value of surface roughness for the aluminum oxide and silicon carbide. The lowest value of surface roughness gives the best surface finish. The most significant parameter when grinding 1060 aluminum alloy is worktable speed for aluminum oxide. Depth of cut is the significant factor when grinding using silicon carbide. The suitable wheel to grind aluminum alloy is silicon carbide it produce the lowest value of surface roughness. The optimization parameter for both wheels is 10 μm depth of cut with 100 mm/s worktable speed.